Perubahan Sosial Ekonomi dan Pola Pikir Masyarakat dengan Munculnya Objek Wisata Puncak Nirwana Lampung - Riswan; Mardian, Husni; Sava Husada, Hindiana (STIES ALIFA, 2022)
Lampung Province is intensively developing local tourism because natural resources (SDA) are very supportive of the potential for tourism development. One of the tourist attractions is Puncak Nirwana, which is located in Kupang Jernih village, Sukarame II, West Teluk Betung District, Bandar Lampung City. The progress of the current tourism economy is very strategic. Many local residents are motivated to make progress on tourism potential in their respective areas. With the increase in the tourism economy, it is one of the projects that can provide benefits for local residents. This is also driven by the progress of the tourism economy which is currently skyrocketing and provides benefits for many parties. This research was conducted using a qualitative method and a descriptive approach. The emergence of the Puncak Nirwana Lampung tourist attraction has clearly had an impact on changing socio-economic conditions for the surrounding community, apart from changing the income of the local community, the emergence of the Puncak Nirwana Lampung tourist attraction has changed the mindset and perspective of the community, where people are more open and motivated to learn about managing tourist attractions. promotion for the progress of their environment. The advice given is the need for more serious and consistent management so that the Puncak Nirwana Lampung tourist attraction can survive for a long time and be able to compete again with other tourist attractions.